Discrepancies between Purchasing Power Parities and Exchange Rates under the Law of One Price: A Puzzle (partly) Explained? - Leon Podkaminer (The Vienna Institute for International Economic Studies (wiiw), 2010)
European Comparison Project data (years 1999-2008) are used for an estimation of cross-country systems (AIDS) of consumer demand functions defined over durable and non-durable tradable goods and non-tradable services. General exchange equilibrium models of inter-EU trade generate equalized relative prices of tradable goods. But domestic relative prices of services become more dispersed and can move the PPP/ER ratios away from unity. PPP/ER discrepancies may be sustained even when there are no impediments to free trade.
Keywords: F11; F15; D12; D58; F31; O57; 330; Purchasing Power Parity; exchange rate; PPP/ER discrepancy; Law of One Price; Balassa-Samuelson Effect; trade integration; computable general equilibrium; cross-country systems of demand functions; Almost Ideal Demand System; tradable goods; non-tradable goods